Hantavirus Cardiopulmonary Syndrome and Diffuse Alveolar Hemorrhage in the Era of COVID-19 - Khizar Hamid; Swaminathan Perinkulam Sathyanarayanan; Touba Naim; Muhammad Hamza; Mirza Omer Mahmood Baig; Emad Abu Sitta (Case Reports in Infectious Diseases)
Hantavirus Cardiopulmonary Syndrome (HCPS) can occur after infection with Hantavirus which can occur by inhaling aerosolized rodent urine, feces, and saliva contaminated with the virus. It presents with the rapid development of pulmonary edema, respiratory failure, and cardiogenic shock with the hallmark being microvascular leakage. We report a patient with a history of alcohol abuse and recent exposure to mice and sick kittens who presented with cough with sputum production, shortness of breath, orthopnea, and new-onset lower extremity edema. Imaging revealed bilateral infiltrates more common on the left with an unremarkable echocardiogram. Testing for COVID-19, Human Immunodeficiency Virus (HIV), influenza, bacterial pneumonia including tuberculosis and methicillin-resistant Staphylococcus aureus (MRSA), aspergillosis, histoplasmosis, Blastomyces, and Coccidiodes was negative. Bronchoscopy and bronchoalveolar lavage revealed diffuse alveolar hemorrhage (DAH) and were negative for acid-fast bacilli and Nocardia cultures. He was further tested for Hantavirus, Q fever, leptospirosis, toxoplasmosis, and empiric treatment with doxycycline initiated. His Hantavirus IgM antibody came back positive. Human Hantavirus infection occurs after inhalation of infected rodent excreta; fortunately, human-to-human transmission has not been documented. HCPS most commonly occurs due to the Sin Nombre virus (SNV), has a case fatality rate of 50%, and is a notifiable disease in the United States. It has 3 distinct phases, prodromal, cardiopulmonary, and convalescent/recovery. The cardiopulmonary phase occurs from increased permeability of pulmonary capillaries and in severe cases can progress to cardiogenic shock. Diagnosis is based on the presence of IgM and IgG Hantavirus antibodies. Treatment is mainly supportive; however, patients are usually treated with broad-spectrum antibiotics while workup is underway. In animal models, ribavirin and favipiravir are only effective when administered in the prodromal phase. If suspicion of Hantavirus infection exists, early mobilization to the intensive care unit for treatment is recommended. Extracorporeal membrane oxygenation (ECMO) has been suggested to improve outcomes in severe HCPS with refractory shock.